Nilai Teologi Hindu Kaharingan Terhadap Komodifikasi Lilis Lamiang - Kunti Ayu Vedanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Commodification today penetrates various aspects of life, including Lilis Lamiang as one of the means of Hindu Kaharingan religious ceremonies. Commodification of Lilis Lamiang has various impacts, one of which causes a decrease in people's understanding to Kaharingan Hindus about the value of Kaharingan Hindu theology on Lilis Lamiang. Based on this phenomenon, researchers conducted an in-depth study using qualitative methods using literature data and interviews with clergy to find answers to problems about the value of Kaharingan Hindu theology to lilis lamiang commodification. This study is needed to avoid the extinction of Lilis Lamiang's value which affects kaharingan Hindus' belief in their religion. In addition, this research was able to enrich the study related to Kaharingan Hindu religion and its dynamics. The results of this study found the value of Kaharingan Hindu theology in Lilis Lamiang, namely as a symbol of Kaharingan Hindu beliefs against Ranying Hatalla Langit as written in The Panaturan Scripture Article 27. Furthermore, commodification of Lilis Lamiang is acceptable as long as it does not exceed the limit. In addition, modifications that appear along with commodification are considered capable of giving a new color in the use of Lilis Lamiang, making it more beautiful.Keywords: komodifikasi, teologi Hindu Kaharingan, Lilis Lamiang